Pendekatan Kritis Implementasi Akad Wadiâah pada Perbankan Syariah Indonesia - Candrakusuma, Muslih (FALAH Jurnal Ekonomi Syariah, 2016)
As a natural situation, the Islamic banking industry not only have a chance, but also the various problems such as problem on products giro and saving syariah based on wadiâah. In wadiâah saving, bank syariah receive trustful saving from the client and distributing it to use it optimally. Actually, the use of trustful saving (wadiâah) is forbidden, but what is applied in the banking industry is wadiâah used to any project of business. From this point of view, this kind of application more relevant to qard contract than wadiâah. The purpose of Islamic lawÂ (maqasid al-shariâah) is to ensure the wealth (hifz al-mal) embodied in the product save deposit box. In save deposit box, wealth entrusted in bank, stored in a special place, that are guarded by the bank. At the level of primary (al-daruriyah), safeguarding the wealth is a basic need for Muslim. So that, the sustainability of safeguarding of wealth should be championed.